Synonymy [Tareduf] in Arabic Language and Qur'anic Studies - Sayyedeh Vahideh Rahimi (تحقیقات علوم قرآن و حدیث, 2007)
The Predecessors, by collecting numerous names or attributes (adjectives) for one or several named entities, without referring to the term "taraduf" (synonymy), have presented some simple or a little various lexicons which eventually led to the formation of greater lexicons. Taking advantage of this introduction, we can probably say that the first lexicographers were synonym-graphics, "Ikhtilaf-i Alfas" (diversity of the words and "Ittifaq-e ma'ani" (unity of the senses) were also some other terminologies in this concern. In addition to these grounds, the goal was prosecuted in other various subjects as well. After the third century, the term "taraduf" found its way into books and replaced the previous terms. Rumania and Ibn-e Faris were introduced to be the first ones to apply the term "taraduf". However, deliberating on some people such as Hamadani and Tirmadzi we find out that they were the first who did it and thus, the formers lose the mentioned priority. Therefore, the historical background of the usage of term changes a  little, going back even further. There exists a specific relation between the meaning of the derivatives of "r-d-f" in the Qur'an and the terminological concept of "taraduf", i.e., the absence of total agreement of words. This justifies the Predecessors' assumption in absence of total synonymy. In some subjects of the Qur'ranic studies, is synonymy mentioned as in that of "the seven letters" wherein, based upon the rational and narrative reasons, they should be excluded from the subject. But in other subjects as: "emphasis, analogue verses and interpretation" the clarified definition of synonymy must be taken into consideration. Synonymy may be included in such subjects if taken according to the definition given by the Predecessors.